Exploring the melodies of opportunity: do nepo babies pursue music out of genuine passion or is it a matter of engaging in musicpreneurship? - Eugine Tafadzwa Maziriri; Brain Mabuyana; Brighton Nyagadza; Mufaro Dzingirai; Tafadzwa C. Maramura (Business Analyst)
Purpose – In recent years, a number of privileged individuals have entered the music industry in Zimbabwe, either as performers or entrepreneurs. The economic challenges in the country may have prompted these individuals to invest in music as a means of diversifying their income or exploring new business opportunities. To determine whether their interest in music is driven by entrepreneurship or genuine passion, a scholarly examination was deemed necessary. Design/methodology/approach – A qualitative research approach with semi-structured interviews was used as the data collection technique. Narrative analysis was conducted on a sample of musicology students in Gweru, Zimbabwe. Findings – The findings revealed the nepo babies’ interest in music is driven by legacy continuation – the responsibility to carry on with the name of the parent – harsh economic conditions, capitalizing on Internet and digital opportunities and mechanisms for psychological satisfaction during hardships. Originality/value – Although there is a wide range of literature on musicpreneurship, there are gaps in studies that have examined whether a nepo baby's interest in music is motivated by musicpreneurship or a genuine passion for it. Therefore, the aim of this research is to contribute to the existing body of literature on African musicpreneurship, with a specific focus on Zimbabwe.